Odpowiedzi

2010-03-21T08:55:56+01:00
Sin(x + π/6) + sin(x - π/6) = - √6/2 i x ∈ <0, 2π>

korzystamy ze wzoru na sumę sinusów:
2sin[(x + π/6 + x - π/6)/2]*cos[(x + π/6 - x + π/6)/2] = - √6/2
2sin(x)*cos(π/6) = - √6/2
2sin(x)*√3/2 = - √6/2
sin(x) = - √2/2
sin(-x) = √2/2
- x = π/4 + 2kπ
x = - π/4 - 2kπ
x = 7π/4 + 2kπ; k ∈ C

√3cosx + sinx - √2 = 0

korzystamy z metody kąta pomocniczego:
√3cosx + sinx = √2
tgφ = √3
tgφ*cosα + sinα = √2
sinφ*cosα + cosφ*sinα = √2*cosφ
sin(φ + α) = √2*cosφ
sin(α + π/6) = √2/2
α + π/6 = π/4 + 2kπ
α = π/12 + 2kπ; k ∈ C

jak masz pytania to pisz na pw